2000
DOI: 10.1083/jcb.150.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mobility of the Alternate Splicing Factor (Asf) through the Nucleoplasm and Steady State Speckle Compartments

Abstract: Compartmentalization of the nucleus is now recognized as an important level of regulation influencing specific nuclear processes. The mechanism of factor organization and the movement of factors in nuclear space have not been fully determined. Splicing factors, for example, have been shown to move in a directed manner as large intact structures from sites of concentration to sites of active transcription, but splicing factors are also thought to exist in a freely diffusible state. In this study, we examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
173
2
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(201 citation statements)
references
References 32 publications
(61 reference statements)
25
173
2
1
Order By: Relevance
“…These findings are consistent with numerous studies on the mobilities of nuclear proteins that have demonstrated rapid exchange between the nucleoplasm and speckles (Kruhlak et al, 2000;Phair and Misteli, 2000;Molenaar et al, 2004), the nucleolus (Phair and Misteli, 2000;Snaar et al, 2000;Chen and Huang, 2001), and Cajal bodies (Snaar et al, 2000;Handwerger et al, 2003;Dundr et al, 2004). We also show here that the SC35 protein is extremely dynamic in both within and outside speckles.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These findings are consistent with numerous studies on the mobilities of nuclear proteins that have demonstrated rapid exchange between the nucleoplasm and speckles (Kruhlak et al, 2000;Phair and Misteli, 2000;Molenaar et al, 2004), the nucleolus (Phair and Misteli, 2000;Snaar et al, 2000;Chen and Huang, 2001), and Cajal bodies (Snaar et al, 2000;Handwerger et al, 2003;Dundr et al, 2004). We also show here that the SC35 protein is extremely dynamic in both within and outside speckles.…”
Section: Discussionsupporting
confidence: 80%
“…Our results do not rule out the presence of a very small slowmoving or immobile class of poly(A) RNA in the nucleus, but if it exists, our results indicate that it is Ͻ5% of the total poly(A) RNA and is present in similar amounts in both speckles and the nucleoplasm. Therefore, it is unlikely that poly(A) RNA serves as an immobile scaffolding to form the speckle; rather, it can move freely in and out of speckles in all directions and visit other speckles.These findings are consistent with numerous studies on the mobilities of nuclear proteins that have demonstrated rapid exchange between the nucleoplasm and speckles (Kruhlak et al, 2000;Phair and Misteli, 2000;Molenaar et al, 2004), the nucleolus (Phair and Misteli, 2000;Snaar et al, 2000;Chen and Huang, 2001), and Cajal bodies (Snaar et al, 2000;Handwerger et al, 2003;Dundr et al, 2004). We also show here that the SC35 protein is extremely dynamic in both within and outside speckles.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…However, after blocking transcription, we found that almost all of the above-mentioned dynamic events ceased, indicating that these dynamic events are also related to transcriptional activities in the plant nuclei. Similar dynamic events were also observed in mammalian cell nuclei (Misteli et al, 1997;Kruhlak et al, 2000;Phair and Misteli, 2000).…”
Section: The Organization and Dynamics Of Plant Sr Proteins Are Depensupporting
confidence: 58%
“…However, after blocking transcription, we found that almost all of the above-mentioned dynamic events ceased, indicating that these dynamic events are also related to transcriptional activities in the plant nuclei. Similar dynamic events were also observed in mammalian cell nuclei (Misteli et al, 1997;Kruhlak et al, 2000;Phair and Misteli, 2000).It is well documented that splicing of most pre-mRNAs occurs cotranscriptionally in mammalian cells (for review, see Proudfoot et al, 2002). As transcription inhibition does not disassemble the speckles in plant nuclei, and the distribution of splicing factors in highly metabolic cells such as meristematic cells is more diffuse, we propose that the plant speckles are storage or modification/assembly sites of splicing components, from which splicing factors or preassembled spliceosome subcomplexes are recruited to transcription sites similar to that suggested for their mammalian counterparts (for review, see Lamond and Spector, 2003).…”
supporting
confidence: 50%